Identifikasi Resiko pada Proses Pengujian Bahan Kimia di Laboratorium PT. ABC Balikpapan - K. Rusba; Maslina Maslina; S. Purwanti; Hardiyono Hardiyono; J.E.A. Liku; I. Siboro; L.M. Zainul; S. Hartono (PKimia FKIP Universitas Halu Oleo, 2021)
Chemical laboratories in the company are included in the work area that has a hazard and high risk. Therefore, effective safety management is required to control the risk of. Research on initial risk assessment and end risk and effectiveness of risk control in the activities of practicum finalizing bottle test in laboratory of PT. ABC Balikpapan. Assess the level of risk on activities in the chemical laboratory of PT. ABC. Hazard identification method finalizing bottle test using task risk analysis, while for risk analysis is done using semi-quantitative risk analysis method with risk assessment criteria (consequence, likelihood) and risk control is also made and then analyzed the result. The results of the average major risk of the end of the initial risk indicating that risk control in the activities of practicum chemical bottle Test finalizing in the laboratory of PT. ABC is good, but there are some high risk value of the end, such as the risks associated with the incidence of fire and explosion. So it is necessary to improve the laboratory safety management through the risk analysis program at every practice activity in the laboratory of PT. ABC.